Influence of Socio-Economic Factors on Wages in Small and Medium-Sized Enterprises - Pinkovetskaya, Yuliya Semenovna (Economy of Regions, 2020)
Small and medium-sized enterprises (SMEs) are not sufficiently developed in Russia, which is largely due to significant gap between the wages of SMEs employees and the wages of workers from other enterprises. Thus, it is essential to examine factors that influence the wages of SMEs workers. The study assesses the influence of various regional socio-economic factors on the wages of employees in small and medium-sized enterprises. The considered factors include the unemployment rate, income of inhabitants, and regional budget expenditures. The paper investigates the relationship between the average monthly wage of SMEs employees and subsistence level in each region. The model uses the official statistics for 82 Russian regions obtained in 2015. The assessed three-factor power regression model describes the dependence of the average monthly wage on specific indicators of the unemployment rate of economically active population, average monthly income, budget expenditures per inhabitant in each region. The density function of normal distribution was used to analyse the ratio of wages of SMEs employees to the regional subsistence level. The article demonstrates a link between wages of SMEs employees and the three studied factors, proving that wages increase with a decrease in unemployment rate and growth of inhabitants’ income and budget expenditures. This fact indicates the high quality of the corresponding regression model. The conducted analysis shows that the wages of SMEs workers significantly differ in various regions of the Russian Federation. The paper proposes tools for assessing wages in SMEs and identifying low-wage regions, which eventually can ensure enterprise development. Further research aims to consider wages in small and medium-sized enterprises belonging to different economic sectors.